PENGEMBANGAN MEDIA PEMBELAJARAN ULTAMA UNTUK MENINGKATKAN MOTIVASI BELAJAR SISWA KELAS VII DI SMPN 2 NGULING - Priyanti, Rizki Islamia; Afifah, Ani; Khoiri, Miftahul (Trigonometri: Jurnal Matematika dan Ilmu Pengetahuan Alam, 2024)
This study aims to develop mathematical snakes and ladders as a learning medium to improve the learning motivation of class VII students at SMPN 2 Nguling. The form of educational problems is the lack of facilities and infrastructure, so educators are required to be innovative to improve the quality of learning, for example developing learning media. An example of learning media that is not boring and the latest is game-based learning media, for example the Ultama game. The research method used in this implementation is research and development accompanied by the ADDIE development model. Data collection techniques using questionnaires, post-tests, observations. The output findings according to the validation of material and media experts show that the developed media gets an average score of 4.42 with a very feasible category. The practicality of the media is seen from the observations of educators carried out by 2 observers obtained IO = 4.50 with a high category and student observations obtained IO = 4.22 with a high category, so it is practical to use. The results of the effectiveness of the results of the student post-test after using Ultama media obtained a percentage of completion of 72% with good criteria, so it is effective to use. Ultama learning media can increase learning motivation with an average individual score increasing from 78.65% to 84.24%. Based on the assessment that has been done, the media developed is feasible, practical, and efficient to be used as a learning media in mathematics learning. Penelitian ini memiliki tujuan guna perkembangan ular tangga matematika selaku media pembelajaran guna peningkatan motivasi belajar siswa kelas VII pada SMPN 2 Nguling. Bentuk permasalahan pendidikan ialah kurangnya fasilitas serta sarana, sehingga pendidik diharuskan inovatif untuk peningkatan mutu pembelajaran misalnya mengembangkan media pembelajaran. Contoh media pembelajaran yang tidak membosankan serta terbaru yaitu media pembelajaran berbasis permainan misalnya permainan ultama. Metode penelitian yang dipakai di pelaksanaan ini ialah pendekatan pengembangan (research and development) disertai model pengembangan ADDIE. Teknik pengambilan data dengan menggunakan kuesioner, post-test, pengamatan. Output temuan menurut validasi ahli materi serta media menunjukan media yang dikembangkan mendapatkan rerata skor sejumlah 4,42 disertai kategori sangat layak. Kepraktisan media dilihat dari observasi pendidik yang dilakukan 2 observer diperoleh IO = 4,50 dengan kategori tinggi dan observasi siswa diperoleh IO = 4,22 dengan kategori tinggi, sehingga praktis digunakan. Hasil keefektifan dari hasil post-test siswa setelah menggunakan media ultama memperoleh persentase ketuntasan 72% dengan kriteria baik, sehingga efektif digunakan. Media pembelajaran ultama bisa menaikkan motivasi belajar disertai rerata skor individu naik dari 78,65% menjadi 84,24%. Berdasarkan penilaian yang telah dilakukan, media yang dikembangkan layak praktis, serta efisien dipakai selaku media pembelajaran dalam pembelajaran matematika.